Evaluation of long-term cardiac side effects of anthracycline chemotherapy by conventional and non-conventional echocardiographic methods in childhood cancer survivors. (20th June 2019) - Yoldaş, Tamer; Yeşil, Şule; Karademir, Selmin; Şahin, Gürses; Arman Örün, Utku; Doğan, Vehbi; Özgür, Senem
Abstract: Objective: Anthracycline chemotherapeutic agents carry the well-recognised risk of cardiac toxicity. The aim of this study was to determine the long-term effect of anthracycline chemotherapy on the biventricular function in childhood cancer survivors using tissue Doppler imaging and two-dimensional speckle tracking echocardiography. Patients and Methods: The study included 45 survivors of childhood cancers and 50 healthy age-matched control patients. Cardiac function was prospectively studied with conventional echocardiography, tissue Doppler imaging, and speckle tracking echocardiography after completion of treatment. The same analysis was performed on matched controls. Results: There was no difference in age, gender, height, and weight between the study and control groups. The mean anthracycline dose was 240 ± 106 mg/m 2 and the mean remission duration was 8.2 ± 5 years (1–20 years) in the study group. Conventional echocardiography showed similar ejection fraction, shortening fraction, and left ventricle end-diastolic diameter in both groups. Mitral lateral and septal tissue Doppler imaging showed normal but according to control group relatively sub-normal systolic and diastolic function in patient group. The global longitudinal and circumferential strain and strain rates were significantly lower in the patient group compared to control group. Correlation analysis revealed a negative and significant correlation between total anthracycline dose and global longitudinal and circumferential strain and strain rates. Conclusion: Sub-clinical systolic and diastolic dysfunction may not be detected by conventional echocardiographic methods which are frequently used in daily practice. Sub-clinical systolic and diastolic dysfunction may be detected more sensitively by echocardiographic method such as speckle tracking echocardiography in childhood cancer survivors.